IMF Survey, Volume 35, Issue 16. (IMF Survey; IMF Survey ;, 2006)
U.S. fiscal outlook; U.S. inflation dynamics; Ireland, FYR Macedonia, El Salvador, Uruguay briefs; Egypt: growth and reform; Canadian female labor participation; EU: Stability and Growth Pact; Suspension of Doha talks; challenges of globalization.